Boundedness of Sublinear Operators with Rough Kernels on Weighted Morrey Spaces. (9th April 2013) - Shi, Shaoguang; Fu, Zunwei
Abstract : The aim of this paper is to get the boundedness of a class of sublinear operators with rough kernels on weighted Morrey spaces under generic size conditions, which are satisfied by most of the operators in classical harmonic analysis. Applications to the corresponding commutators formed by certain operators and BMO functions are also obtained.